38 'The right information to the right people at the right time'- design and delivery of a palliative medicine education programme during COVID-19. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Doherty, Catherine; Hutcheson, Sinead
Abstract : In the face of an overwhelming Coronavirus pandemic, Palliative Medicine guidelines, knowledge and skills are a crucial aspect of care for many seriously affected patients. Palliative care specialists can only treat a minority of dying patients therefore an educational intervention was needed to equip frontline staff. The education programme was delivered via a live virtual platform in weekly 1 hour education sessions. These were offered to community and hospital facing multidisciplinary staff within the Belfast Trust. Each session was followed by a live Q&A with specialist staff. A total of 11 sessions delivered over 13 weeks reached approximately 528 health care professionals.Downar et al 1 described four critical elements for palliative care provision in a pandemic - 'stuff', 'staff', 'space' and 'systems'. Program topics therefore included: Recognising dying Symptom Assessment and Management for patients with COVID 19 Advance Care Planning After death care Bereavement care Self Care The advantages of virtual education include accessibility, affordability and flexibility. We conclude that it is possible to successfully provide a focused educational intervention on palliative care principles when resources are scarce. Disasters will continue to occur and technologies will play a part in helping us to cope with them. Reference: Downar J, Seccareccia D. Palliating a pandemic: 'All patients must be cared for'. J Pain Symptom Manage 2010;39 :291''5.doi:10.1016/j.jpainsymman.2009.11.241 pmid:20152591